2005
DOI: 10.1111/j.1538-7836.2005.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin enhances functional tissue factor on human glomerular endothelial cells: implications for the pathophysiology of hemolytic uremic syndrome

Abstract: Summary.  Background: The pathogenesis of Shiga toxin (Stx)‐mediated childhood hemolytic uremic syndrome (HUS) is not fully delineated, although current evidence implicates a prothrombotic state. We hypothesized that the tissue factor (TF) pathway plays a major role in the pathophysiology of HUS. Materials and methods: We measured cell surface TF activity in response to tumor necrosis factor‐α (TNF‐α) (20 ng mL−1, 2–144 h), Stx‐1 (10−11 mol L−1, 4–144 h), or their combination (TNF‐α 22 h and Stx‐1 for the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…The role of apoptosis in Stx-mediated disease is also unclear. Several studies utilizing mouse models have observed apoptosis in renal cells following treatment with Stx (23,42,47), while other studies have observed necrosis (10,29,37,46,58,60).…”
Section: Discussionmentioning
confidence: 99%
“…The role of apoptosis in Stx-mediated disease is also unclear. Several studies utilizing mouse models have observed apoptosis in renal cells following treatment with Stx (23,42,47), while other studies have observed necrosis (10,29,37,46,58,60).…”
Section: Discussionmentioning
confidence: 99%
“…We have also observed that cytokine-activated human umbilical vein (macrovascular) endothelial cells (HUVECs) fail to demonstrate further enhancement of the cell-surface TF activity after exposure to Stx, which potentially may explain localization of thrombosis to the microvasculature and account for the specificity of organ involvement in HUS [13]. However, the potential pathogenic or modulatory role of locally produced Ang II in the prothrombotic state that constitutes HUS is largely unknown and has not been addressed in previous in vitro studies.…”
Section: Introductionmentioning
confidence: 93%
“…As we observed no differences between the effect of Stx-1 and Stx-2 in upregulating TF activity in HGECs, we subsequently focused on the effects of Stx-1, which has been used more often in cell culture experiments by other investigators. The concentration of Stx-1 as 10 −11 M was selected based both on the observations of Yagi et al [15], who detected Stx concentration of this order of magnitude in the plasma of patients with HUS, and on our observations that 10 −11 M Stx-1 enhanced TF on TNF-α stimulated HGECs [13].…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stx binds to specific receptors distributed throughout endothelial cells of the gastrointestinal tract, pancreas, brain, and kidney and is responsible for a multitude of cytotoxic, proinflammatory and prothrombotic effects [10]. Systemic complications resulting from Stx include cell death, platelet activation and deposition, cytokine release and increased tissue factor expression on the cells of the microvasculature [11]. Microthrombi formation in the microvasculature following Stx-induced platelet activation results in the abnormal shear stress and disturbances in blood flow that eventually leads to the production of the fragmented red blood cells or schistocytes representative of a microangiopathic anemia.…”
Section: Stec Husmentioning
confidence: 99%